Klinisk fagring som ein kompetanseutviklande metode i kommunehelsetenesta - sjukepleiarar og leiarar sine erfaringar - Hynne, Astrid Bjørnerheim; Torjuul, Kirsti; Paulsen, Bente (Nordisk tidsskrift for helseforskning, 2018)
The purpose of this study was to investigate the experiences of nurses and managers of a clinical circle as a method of competence development, and the way working conditions and contextual factors in the municipality affected the process of learning and cooperation between nurses and managers.Focus group interviews were conducted with five nurses and five managers. The interviews that were analyzed using qualitative content analysis resulted in three maincategories: cooperation across different units, shared clinical theme, and contextual factors. The findings indicate that participating in a clinical circle provide nurses with opportunities to develop their clinical competence through sharing knowledge and experiences, and by searching, assessing and implementing research findings into practice. In order to establish and sustain a clinical circle, the findings indicate that it may be useful to prearrange contextual factors, such as leadership expectancy, and timereserved for clinical circle work.